Influence of Supplementing Giloe and Cinnamon on Production Performance in Commercial Broiler Chicken - Tiwari, Garima; Rahal, Anshu; Kumar, Ashok; Kumar, Anil (Indian Journal of Animal Nutrition, 2019)
Feeding trial of 42 days was conducted to study the effect of dietary incorporation of giloe and cinnamon powder on growth performance in commercial broilers. A total of 120, day-old broiler chicks were divided randomly into 6 treatment groups with 2 replicates of 10 chicks each viz., T1 (control) were fed basal diet whereas in treatment group T2, T3, T4, T5 and T6,basal diet was incorporated with 1% giloe, 2% giloe, 1% cinnamon, 2% cinnamon and combination of 1% giloe and 1% cinnamon, respectively. During the whole experimental period (0-42 days), incorporation of 1 % giloe improved broiler performance in terms of body weight, weight gain, feed conversion ratio and performance index. The average body weight gain of T1,T2, T3, T4, T5 and T6 were 1408.2, 1580.2, 1540.3, 1517.2, 1474.4 and 1551.0, respectively. The results of growth performance of broilers on incorporation of 1% giloe and 1% cinnamon in combination are also beneficial. It is concluded that 1% giloe alone or in combination with 1%cinnamon can be fed to commercial broilers to improve growth parameters.